Optimalisasi Penerapan Diversi dalam Penanganan Anak sebagai Kurir Narkotika; Revisi Regulasi dan Dukungan Sosial - Audrey, Jessica; Adhari, Ade (IAIN Langsa, 2025)
This study aims to explore the optimization of the implementation of diversion in handling children involved as drug couriers, with a focus on the legal regulation revisions and social support required. The research uses a normative legal study methodology with a qualitative approach, relying on descriptive analysis of existing regulations and relevant scholarly journals. The primary data sources consist of laws and regulations on juvenile criminal justice, while secondary sources are derived from legal literature published in the last ten years. The findings conclude that diversion plays an important role in addressing cases of children involved as drug couriers, but its implementation in Indonesia is still hindered by insufficiently comprehensive legal policies and inadequate social support, thus requiring regulatory revisions and inter-agency coordination to ensure its effectiveness. Social support, such as rehabilitation programs, alternative education, and economic empowerment, is crucial to creating new opportunities for these children, while technology can strengthen monitoring and evaluation of the diversion process to ensure its continuity as a rehabilitation effort based on restorative justice principles.